2012
DOI: 10.1016/j.actamat.2012.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Transition of solidification mode and the as-cast γ grain structure in hyperperitectic carbon steels

Abstract: Formation processes of as-cast γ grain structures during casting of hyperperitectic carbon steels with 0.15-0.45 mass% carbon concentrations have been studied by means of a rapid unidirectional solidification technique. In steels with 0.15-0.41 mass% carbon concentrations, coarse columnar γ grains (CCG) with a minor axis diameter of 1-3mm developed along the direction of temperature gradient. In a steel with 0.38 mass% carbon, importantly, columnar γ grains (CG) whose minor axis diameter is less than 500 μm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 20 publications
(37 reference statements)
2
24
0
Order By: Relevance
“…The mechanism of formation of CCGs in hyperperitectic carbon steels was investigated in our recent works [7,8] using rapid unidirectional solidification equipment which realizes the cooling conditions similar to those near the slab surface in the practical continuous casting. The schematic illustration of the microstructure during the formation process of CCGs is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of formation of CCGs in hyperperitectic carbon steels was investigated in our recent works [7,8] using rapid unidirectional solidification equipment which realizes the cooling conditions similar to those near the slab surface in the practical continuous casting. The schematic illustration of the microstructure during the formation process of CCGs is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent investigations revealed that the formation of the CCG structure originates from the discontinuous grain growth process from fine columnar γ grain (FCG) structure which forms in liquid + γ two-phase field [9,10] . In addition, the theoretical relationship for the critical condition for the occurrence of the discontinuous grain growth given by Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Fig. 1 Schematic illustrations of (a) rapid unidirectional solidification equipment used in the previous study [9,10] and (b) typical microstructure during the discontinous grain growth proces observed in the quenched sample. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations